Reducing Coastal Risk on the East and Gulf Coasts - National Research Council (The National Academies Press, 2014)
Hurricane- and coastal-storm-related losses have increased substantially during the past century, largely due to increases in population and development in the most susceptible coastal areas. Climate change poses additional threats to coastal communities from sea level rise and possible increases in strength of the largest hurricanes. Several large cities in the United States have extensive assets at risk to coastal storms, along with countless smaller cities and developed areas. The devastation from Superstorm Sandy has heightened the nation's awareness of these vulnerabilities. What can we do to better prepare for and respond to the increasing risks of loss? Reducing Coastal Risk on the East and Gulf Coasts reviews the coastal risk-reduction strategies and levels of protection that have been used along the United States East and Gulf Coasts to reduce the impacts of coastal flooding associated with storm surges. This report evaluates their effectiveness in terms of economic return, protection of life safety, and minimization of environmental effects. According to this report, the vast majority of the funding for coastal risk-related issues is provided only after a disaster occurs. This report calls for the development of a national vision for coastal risk management that includes a long-term view, regional solutions, and recognition of the full array of economic, social, environmental, and life-safety benefits that come from risk reduction efforts. To support this vision, Reducing Coastal Risk states that a national coastal risk assessment is needed to identify those areas with the greatest risks that are high priorities for risk reduction efforts. The report discusses the implications of expanding the extent and levels of coastal storm surge protection in terms of operation and maintenance costs and the availability of resources. Reducing Coastal Risk recommends that benefit-cost analysis, constrained by acceptable risk criteria and other important environmental and social factors, be used as a framework for evaluating national investments in coastal risk reduction. The recommendations of this report will assist engineers, planners and policy makers at national, regional, state, and local levels to move from a nation that is primarily reactive to coastal disasters to one that invests wisely in coastal risk reduction and builds resilience among coastal communities.
Keywords: Earth Sciences

Review of the EPA's Economic Analysis of Final Water Quality Standards for Nutrients for Lakes and Flowing Waters in Florida - National Research Council (The National Academies Press, 2012)
The Environmental Protection Agency's estimate of the costs associated with implementing numeric nutrient criteria in Florida's waterways was significantly lower than many stakeholders expected. This discrepancy was due, in part, to the fact that the Environmental Protection Agency's analysis considered only the incremental cost of reducing nutrients in waters it considered "newly impaired" as a result of the new criteria-not the total cost of improving water quality in Florida. The incremental approach is appropriate for this type of assessment, but the Environmental Protection Agency's cost analysis would have been more accurate if it better described the differences between the new numeric criteria rule and the narrative rule it would replace, and how the differences affect the costs of implementing nutrient reductions over time, instead of at a fixed time point. Such an analysis would have more accurately described which pollutant sources, for example municipal wastewater treatment plants or agricultural operations, would bear the costs over time under the different rules and would have better illuminated the uncertainties in making such cost estimates.
Keywords: Environment and Environmental Studies

Measuring and Removing Dissolved Metals from Stormwater in Highly Urbanized Areas - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2014)
TRB’s National Cooperative Highway Research Program (NCHRP) Report 767: Measuring and Removing Dissolved Metals from Stormwater in Highly Urbanized Areas presents prototype best management practices (BMPs) for the removal of dissolved metals in stormwater runoff.The report presents three conceptual configurations in detail: two vault system configurations for urban and rural settings, and an inlet scupper with media for bridge deck drainage systems.The report also includes standard protocols to accurately measure the levels of dissolved metals in stormwater. Practical guidance on the use of these protocols is provided in an appendix to the final report. The report is accompanied by an Excel spreadsheet on CD designed to assist in sizing the filter bed in the vaults and the bridge deck inlet scupper.The CD is also available for download from TRB’s website as an ISO image. Links to the ISO image and instructions for burning a CD from an ISO image are provided below.Help on Burning an .ISO CD ImageDownload the .ISO CD ImageCD Disclaimer - This software is offered as is, without warranty or promise of support of any kind either expressed or implied. Under no circumstance will the National Academy of Sciences or the Transportation Research Board (collectively "TRB") be liable for any loss or damage caused by the installation or operation of this product. TRB makes no representation or warranty of any kind, expressed or implied, in fact or in law, including without limitation, the warranty of merchantability or the warranty of fitness for a particular purpose, and shall not in any case be liable for any consequential or special damages.
Keywords: Transportation and Infrastructure

Dam and Levee Safety and Community Resilience: A Vision for Future Practice - National Research Council (The National Academies Press, 2012)
Although advances in engineering can reduce the risk of dam and levee failure, some failures will still occur. Such events cause impacts on social and physical infrastructure that extend far beyond the flood zone. Broadening dam and levee safety programs to consider community- and regional-level priorities in decision making can help reduce the risk of, and increase community resilience to, potential dam and levee failures. Collaboration between dam and levee safety professionals at all levels, persons and property owners at direct risk, members of the wider economy, and the social and environmental networks in a community would allow all stakeholders to understand risks, shared needs, and opportunities, and make more informed decisions related to dam and levee infrastructure and community resilience. Dam and Levee Safety and Community Resilience: A Vision for Future Practice explains that fundamental shifts in safety culture will be necessary to integrate the concepts of resilience into dam and levee safety programs.
Keywords: Earth Sciences

Desalination: A National Perspective - National Research Council (The National Academies Press, 2008)
There has been an exponential increase in desalination capacity both globally and nationally since 1960, fueled in part by growing concern for local water scarcity and made possible to a great extent by a major federal investment for desalination research and development. Traditional sources of supply are increasingly expensive, unavailable, or controversial, but desalination technology offers the potential to substantially reduce water scarcity by converting the almost inexhaustible supply of seawater and the apparently vast quantities of brackish groundwater into new sources of freshwater.
Keywords: Earth Sciences; Environment and Environmental Studies

Urban Stormwater Management in the United States - National Research Council (The National Academies Press, 2009)
The rapid conversion of land to urban and suburban areas has profoundly altered how water flows during and following storm events, putting higher volumes of water and more pollutants into the nation's rivers, lakes, and estuaries. These changes have degraded water quality and habitat in virtually every urban stream system. The Clean Water Act regulatory framework for addressing sewage and industrial wastes is not well suited to the more difficult problem of stormwater discharges.
Keywords: Environment and Environmental Studies

Using Graywater and Stormwater to Enhance Local Water Supplies: An Assessment of Risks, Costs, and Benefits - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Chronic and episodic water shortages are becoming common in many regions of the United States, and population growth in water-scarce regions further compounds the challenges. Increasingly, alternative water sources such as graywater-untreated wastewater that does not include water from the toilet but generally includes water from bathroom sinks, showers, bathtubs, clothes washers, and laundry sinks- and stormwater-water from rainfall or snow that can be measured downstream in a pipe, culvert, or stream shortly after the precipitation event-are being viewed as resources to supplement scarce water supplies rather than as waste to be discharged as rapidly as possible. Graywater and stormwater can serve a range of non-potable uses, including irrigation, toilet flushing, washing, and cooling, although treatment may be needed. Stormwater may also be used to recharge groundwater, which may ultimately be tapped for potable use. In addition to providing additional sources of local water supply, harvesting stormwater has many potential benefits, including energy savings, pollution prevention, and reducing the impacts of urban development on urban streams. Similarly, the reuse of graywater can enhance water supply reliability and extend the capacity of existing wastewater systems in growing cities. Despite the benefits of using local alternative water sources to address water demands, many questions remain that have limited the broader application of graywater and stormwater capture and use. In particular, limited information is available on the costs, benefits, and risks of these projects, and beyond the simplest applications many state and local public health agencies have not developed regulatory frameworks for full use of these local water resources. To address these issues, Using Graywater and Stormwater to Enhance Local Water Supplies analyzes the risks, costs, and benefits on various uses of graywater and stormwater. This report examines technical, economic, regulatory, and social issues associated with graywater and stormwater capture for a range of uses, including non-potable urban uses, irrigation, and groundwater recharge. Using Graywater and Stormwater to Enhance Local Water Supplies considers the quality and suitability of water for reuse, treatment and storage technologies, and human health and environmental risks of water reuse. The findings and recommendations of this report will be valuable for water managers, citizens of states under a current drought, and local and state health and environmental agencies.
Keywords: Earth Sciences; Environment and Environmental Studies

Prospects for Managed Underground Storage of Recoverable Water - National Research Council (The National Academies Press, 2008)
Growing demands for water in many parts of the nation are fueling the search for new approaches to sustainable water management, including how best to store water. Society has historically relied on dams and reservoirs, but problems such as high evaporation rates and a lack of suitable land for dam construction are driving interest in the prospect of storing water underground. Managed underground storage should be considered a valuable tool in a water manager's portfolio, although it poses its own unique challenges that need to be addressed through research and regulatory measures.
Keywords: Earth Sciences; Environment and Environmental Studies

Funding and Managing the U.S. Inland Waterways System: What Policy Makers Need to Know: What Policy Makers Need to Know - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2015)
TRB Special Report 315: Funding and Managing the U.S. Inland Waterways System: What Policy Makers Need to Know explores the role and importance of the federally funded inland waterways system, priorities for future investment, its beneficiaries, and sources of funding.In recent years, the inland waterways system has transported six to seven percent of all domestic ton-miles of cargo. The system is a small but important component of the national freight system, particularly for bulk commodities. The study committee finds that, in order to ensure efficient use of limited navigation resources, the most critical need for the inland waterways system is a sustainable and well-executed plan for maintaining system reliability and performance. Reliability and performance will depend on placing higher priority on investments in operations and maintenance (O&M). Without a funding strategy that prioritizes system preservation, maintenance may continue to be deferred, which would result in further deterioration and in a less cost effective and less reliable system.The committee finds that more reliance on a “user-pays” funding strategy for the commercial navigation system is feasible, would generate new revenues for maintenance, and would promote economic efficiency.The committee suggests that an asset management program focused on economic efficiency, fully implemented and linked to the budgeting process, would help prioritize maintenance spending and ascertain the funding levels required for reliable freight service.View the TRB Special Report 315 webcast.View the press release.
Keywords: Transportation and Infrastructure